2021
DOI: 10.1007/s10649-021-10063-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring adults’ awareness of and suggestions for early childhood numerical activities

Abstract: This study focuses on adults who are neither preschool teachers nor professional caregivers and investigates their beliefs regarding the importance of engaging young children with numerical activities. It also examines the types of numerical activities adults report having observed children engaging with, as well as the types of activities they propose as a way for promoting counting, enumerating, recognizing number symbols, and number composition and decomposition. Findings showed that participants believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The role of ECA teaching is to provide children with experiences that would help them reach an overall understanding of numbers and develop flexible ways of working with them, beginning with an intuitive and informal encounter with numbers, followed by a formal and symbolic understanding of the various representations of numbers as required at school (Baroody et al, 2006). Therefore adults, including early-childhood teachers, have an important role in the mathematical development of young children (Levenson et al, 2021). Studies have indicated a relation between the development of children's mathematical knowledge and the specific mathematical discourse that their teachers conducted with them (Gjicali et al, 2019;Purpura et al, 2017;Uscianowski et al, 2020).…”
Section: Early-childhood Mathematics Educationmentioning
confidence: 99%
“…The role of ECA teaching is to provide children with experiences that would help them reach an overall understanding of numbers and develop flexible ways of working with them, beginning with an intuitive and informal encounter with numbers, followed by a formal and symbolic understanding of the various representations of numbers as required at school (Baroody et al, 2006). Therefore adults, including early-childhood teachers, have an important role in the mathematical development of young children (Levenson et al, 2021). Studies have indicated a relation between the development of children's mathematical knowledge and the specific mathematical discourse that their teachers conducted with them (Gjicali et al, 2019;Purpura et al, 2017;Uscianowski et al, 2020).…”
Section: Early-childhood Mathematics Educationmentioning
confidence: 99%
“…In this paper we present part a large research project that aimed to investigate adults' knowledge and beliefs regarding playful mathematics learning during the early years (e.g., Levenson et al, 2022). As part of the project, we planned and implemented an intervention with adults that focused on enhancing adults' knowledge of playful numerical activities.…”
Section: Introductionmentioning
confidence: 99%